Permian ammonoids: Results and prospects of research in Russia and other post-Soviet states - T.B. Leonova (Учёные записки Казанского университета: Серия Естественные науки)
The paper aims to introduce the history of Russian and Soviet study of Permian ammonoids, from the middle of the 19th century to the present, to a wider audience of geologists, and particularly to a younger generation of students and researchers. Permian ammonoids played the leading role in the substantiation of all stages of the lower series of the Permian (Cisuralian). The Artinskian Stage was first established in the late 19th century by A.P. Karpinsky, the Sakmarian Stage in 1938, and the Asselian Stage in 1954, both by V.E. Ruzhencev. The Carboniferous-Permian boundary was established and ratified based on the changes in assemblages of conodonts, ammonoids, and fusulinids. Its stratotype (GSSP) was officially accepted in the Aidaralash Section, first proposed by V.E. Ruzhencev. Permian ammonoids have been a subject of study since the recognition of the Permian System; the first described Artinskian taxon was Goniatites orbignyanus Verneuil, 1845. The initial stage of the study consisted mainly of the accumulation and generalization of data, including the first attempts to study phylogenesis. It is associated with the names of A.P. Karpinsky, P.I. Krotov, A.A. Chernov, T.M. Emelyantsev and others. The first collections of Permian ammonoids came mainly from the Southern Urals. Then they were discovered in the Darvaz Range and in the Crimea. Major progress was made, both in the study of taxonomic diversity and in the classification of the collected data, in the middle of the 20th century, starting in the 1930s. V.E. Ruzhenсev made a huge contribution to the research of this group of fossils. At the same time, the foundations of onto-phylogenetic studies of ammonoids were developed. The geography of the Permian ammonoid sites has expanded, as reflected in the publication of numerous regional works with monographic descriptions of the ammonoid faunas of the Northeast and Far East of Russia, as well as Central Asia. Currently, Permian ammonoid studies are very diverse, and, along with the description of new taxa, reconstruction and analysis of the phylogenies and morphogenesis of taxa of family rank, include multidisciplinary ecosystem, morphofunctional, and biogeographical research. Ammonoid biostratigraphy also remains in demand.